PEMBELAJARAN IPS MENGGUNAKAN MODEL COOPERATIVE LERNING TIPE GROUP INVESTIGATION (GI) DI KELAS IV SD - Devi, Risvila; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
Purpose of this  research is to describe in creasins students achievement in social subject (IPS) on cooperative learning type group investigation (GI) model at grade students of SDN 17 KayuArokotapadang.This research use qualitative and quantitative approach. Subject of this research are teacher and 22 students. The observation result for cycle I 73,2in crease on cycle II 92,9. The observation result for teacher aspect on cycle I 72,5 increase on cycle II 92,9. The observation result for students aspect on cycle I 70 increase on cycle II 87,5. Students achievement on cycle I 73,9 increase on cycle II 83,3. Key words: student’s learning achievement, Cooperative LearningmodelGroup Invesitgation (GI) type